Small‐sized specimen design with the provision for high‐frequency bending‐fatigue testing. Issue 12 (10th October 2021) - Ghadimi, Hamed; Jirandehi, Arash P.; Nemati, Saber; Guo, Shengmin
Abstract: The testing and study of emerging materials—such as additively manufactured materials—demands for specimen designs that are cost effective and time saving. The design of a small‐sized bending‐fatigue test specimen for an ultrasonic fatigue testing system is reported in this paper. The design is optimized based on the finite element analysis and analytical‐solution results to achieve the proper vibration shape and stress distribution. The proposed design is evaluated in the high‐ and very‐high‐cycle fatigue regimes under 20‐kHz frequency. Both simulation and testing results confirm that the desirable vibration mode occurs and the specimen fails at the designated test (gauge) section, where the maximum stress exists. The stress–life ( S – N ) curve is obtained for Inconel alloy 718 and indicates an expected trend. HIGHLIGHTS: A specimen design for the fatigue bending testing of metals via ultrasonic testers is delivered. The SEM observations of crack initiation/growth indicate failure occurs in the designed gauge section. The analytical, FEM, and experimental studies indicate the desired bending mode occurs at around 20 kHz. The maximum stress/strain location from FEM analysis matches with the failure location.